INFLUENCE OF ARTIFICIAL LUNG VENTILATION ON REAL ENERGY EXPENDITURE VALUE OF SURGICAL INTENSIVE CARE UNIT PATIENTS - I. V. Polyakov; K. N. Zolotukhin; I. N. Leyderman (Креативная хирургия и онкология)
Elective or emergence surgery often is closely connected with development of hypercatabolism-hypermetabolism syndrome. Non-effective and late nutritional support in surgical critically ill patients lead to several consequences and complications such as: wound and nosocomial infectons, gastric stress ulcers, pressure ulcers, prolonged artificial lung ventilation, increased length of stay in ICU and hospital. Energy deficit is one of the important components of critical illness and it corresponds with multiple organ dysfunction progression. Prospective study was provided in 18 beds surgical intensive care unit (SICU). 106 patient medical cards were divided into 4 groupstwo control and two basic with espiratory support (subgroup with artificial lung ventilation and subgroup without artificial lung ventilation). We compared the effectiviness of two methods for the estimation of patients energy needsspecial equations and indirect calorimetry. As a result we found out that main markers of energy and protein metabolism and nutritive status were significantly higher in indirect calorimetry groupswith and without artificial lung ventilation. Conclusion: Indirect calorimetry method usage for the estimation of energy needs in surgical ICU patients is more effective than special equations method during first 7 days of critical illness and may be recommended for clinical practice implication.